The killer shrimp, Dikerogammarus villosus, invading European Alpine Lakes: A single main source but independent founder events with an overall loss of genetic diversity. (17th April 2017) - Rewicz, Tomasz; Wattier, Remi; Rigaud, Thierry; Grabowski, Michał; Mamos, Tomasz; Bącela‐Spychalska, Karolina
Abstract: The effects of biological invasions are generally more detrimental in isolated ecosystems than in the interconnected ones and freshwater lakes appear to be particularly fragile. The Ponto‐Caspian freshwater amphipod Dikerogammarus villosus (Pontogammaridae), also known as the killer shrimp, is a highly invasive species that can have significant ecological impacts on receiving ecosystems. It has colonised most of the European main inland waterbodies, including at least 12 lakes in the Alps – an area of high conservational priority and, at the same time, heavily affected by anthropogenic changes. Particularly, overland translocations of boats among tourist centres may have contributed to colonisation of Alpine lakes by D. villosus . We aimed to answer the following questions: Which of the two genetically differentiated populations invading continental lowland Europe has contributed to colonisation of the Alpine lakes? Is it possible to detect independent founder events in different regions of the Alps and/or secondary spread among European Alpine lakes? Have the lacustrine populations suffered any reduction in genetic variation during colonisation? Twelve populations from the Alpine lakes were genotyped for a portion of mtDNA (COI and 16S) and for seven nuclear microsatellite loci. A wide range of methods was used to analyse the data, including haplotype network, Bayesian clustering and demography tests. Our results show that the lowland western route (Danube‐Rhine waterway) of the killer shrimp invasion was the source for introduction to European Alpine lakes. Unlike invasive populations in the main lowland rivers, most of the Alpine populations suffered bottleneck and had significantly lower genetic diversity compared to their source population along the western route. We found clear patterns of genetic structure, revealing multiple independent lake colonisations followed by secondary spread between lakes. An overland transport of D. villosus with tourist boats is probably the major spreading vector to and among Alpine lakes. Implementing safety programmes such as the 'check, clean, and dry' procedures may stop or slow down spreading of D. villosus among the Alpine lakes, and prevent additional long distance transport.